Letter from Kansas…Interesting to Cattle Drivers (Symphony in the Flint Hills, 2017)
A letter to the editor from G.A.W. in Junction City, Kansas, in the Dallas Daily Herald, 16 May 1868.
Keywords: Dallas Daily Herald; cattle drives; Abilene; Junction City; Kansas